2022
DOI: 10.1063/5.0091738
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking of solitons in the PT-symmetric nonlinear Schrödinger equation with the cubic–quintic competing saturable nonlinearity

Abstract: The symmetry breaking of solitons in the nonlinear Schrödinger equation with cubic–quintic competing nonlinearity and parity-time symmetric potential is studied. At first, a new asymmetric branch separates from the fundamental symmetric soliton at the first power critical point, and then, the asymmetric branch passes through the branch of the fundamental symmetric soliton and finally merges into the branch of the fundamental symmetric soliton at the second power critical point, while the power of the soliton i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Such projects are on the table and the results of those research activities will be soon made visible to the knowledge-hungry scientists. The novel results from additional integration approaches, as well as other forms of analysis, would be disseminated all across that would align with the pre-existing approaches [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Such projects are on the table and the results of those research activities will be soon made visible to the knowledge-hungry scientists. The novel results from additional integration approaches, as well as other forms of analysis, would be disseminated all across that would align with the pre-existing approaches [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, linear spectra of the PT-symmetric systems remain purely real due to the exact balance between the gain and loss, provided that the strength of the gain–loss distribution does not exceed a certain critical value [2027]. And a multitude of intensive research results on PT-symmetric systems have been reported [2843]. Experimentally, setups demonstrating persistent PT symmetry were realized in optics [23,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…When optical solitons propagate in a fiber, they interact with each other, causing local phase changes in the fiber, thereby altering the frequency and waveform of the optical solitons. [27][28][29] Therefore, the NLS equation can not only help us better understand the nonlinear effects in the transmission and interaction of optical solitons, but also provide new solutions and technical means to improve the performance and reliability of nonlinear optical systems. [30][31][32] In this paper, we will study the interaction between two optical solitons based on the NLS equation.…”
Section: Introductionmentioning
confidence: 99%